2001
DOI: 10.1097/00004010-200101000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Just How Integrated Are Integrated Delivery Systems? Results From a National Survey

Abstract: This article examines three emergent processes in physician-hospital integrated delivery systems (IDSs). We find these processes are underdeveloped based on data gathered from a national sample of hospitals drawn from nine health care systems. These processes are also loosely coupled with the structures used to integrate physicians and hospitals, as well as with the environmental context in which they occur. Such loose coupling entails both advantages and disadvantages for IDSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…In many Health Maintenance Organisations, only structures are integrated, the processes and professionals are not better aligned. It seems that these structures are not able to fundamentally change the practice of professionals and the way in which they collaborate [7,8]. But in many countries, there are now successful examples of integrated care, where professionals still work in separate organisations [1].…”
Section: Introductionmentioning
confidence: 99%
“…In many Health Maintenance Organisations, only structures are integrated, the processes and professionals are not better aligned. It seems that these structures are not able to fundamentally change the practice of professionals and the way in which they collaborate [7,8]. But in many countries, there are now successful examples of integrated care, where professionals still work in separate organisations [1].…”
Section: Introductionmentioning
confidence: 99%
“…All too often, however, they failed to develop a common, standardized set of activities across the different IDN components and to closely link the new structures with new organizational processes of providing incentives to physicians, managing medical staffs, and developing leadership. 42 Thus, the structural integration was not accompanied by a processual approach to integration. All too often the structural and processual activities were only loosely linked together, with some disregard for day-to-day operations.…”
mentioning
confidence: 99%
“…Burns et al (2001) found that even when efforts are made to integrate the structural units of hospitals, as is seen in managed care efforts in the U.S., workflow integration lags far behind, and they hypothesized that structural integration and work process integration are only loosely related. Furthermore, Kitchener and Gask (2003) studied mergers in the mental health sector, and found that ''the persistence of Ôloosely coupledÕ practices and structures restricted improvements in collaboration and service co-ordination.''…”
Section: Framework Part 1: Deployment Challengesmentioning
confidence: 99%
“…We specifically note that we are making a general case in this paper, and that, even in North America and in Europe, all health care organizations are not organized in a loosely coupled fashion. However, we feel that there is enough supporting evidence to conclude that loose coupling is common in many healthcare organizations (Burns et al, 2001;Pinelle and Gutwin, 2003;Scheid-Cook, 1990;Scott, 1985), and that it can play a key role in the adoption and utilization of CSCW systems (e.g. Dean, 1993;Littlejohns et al, 2003;Williams, 1992).…”
Section: Introductionmentioning
confidence: 99%